Effects and mechanism of erythropoietin on the cognitive function of kainic acid-induced epileptic rats - Peng HE; Jin-gang GUO (Chinese Journal of Contemporary Neurology and Neurosurgery, 2015)
Objective To observe the effects of erythropoietin (EPO) on the behaviors and abilities of spatial learning and memory of kainic acid (KA)-induced epileptic rats. Methods A total of 96 rats were randomly divided into 4 groups: control group, model group, low-dose EPO pretreated group and high-dose EPO pretreated group. After treatment with relevant reagents, the behaviors of rats in each group were observed. The abilities of spatial learning and memory were evaluated by Morris water maze test. Expressions of apoptosis-related factors: p38MAPK, c-Myc and caspase-3 were detected by Western blotting.  Results Behavior observation showed seizures in EPO groups reduced (P = 0.000). Compared with model group, rats in EPO groups had significantly reduced escape latency in positioning navigation trial (P = 0.043, 0.000), significantly prolonged first quadrant latency (P = 0.000, 0.000) and increased platform crossing index in spatial probe trial (P = 0.000, 0.046), expressly in high-dose EPO group (P = 0.000, for all). Expressions of p38MAPK (P = 0.000, 0.000), c-Myc (P = 0.009, 0.000) and caspase-3 (P =0.003, 0.000) in rat hippocampus were significantly decreased in EPO groups than that in model group, expressly in high-dose EPO group (P = 0.040, 0.030, 0.048).  Conclusions Erythropoietin can reduce the attack of epileptic rats and increase the ability of spatial learning and memory in KA-induced epileptic rats. The mechanism may be associated with depressing the expression of p38MAPK and downstream c-Myc and caspase-3, finally reducing neuronal apoptosis.   DOI: 10.3969/j.issn.1672-6731.2015.05.011